EARLY INTERVENTION TECHNOLOGIES AND MEDICAL SKILLS IN CHILDREN WITH PERINATAL ENCEPHALOPATHY - Alimova Iroda Anvarovna; Raimova Zulfiyakhan Makhamatjonovna (Scholar Express Journal, 2023)
This article provides information on early intervention technologies and medical skills in children with perinatal encephalopathy
Keywords: Perinatal encephalopathy; nervous diseases; central nervous system; brain